Multicultural education policies in the Spanish region of Castilla La Mancha - Alonso Mateo Gómez; Raquel Bravo Marín (Educational Role of Language Journal, 2020)
Multiculturalism as the coexistence in the same society of persons from different cultures poses a challenge to our contemporary societies. The role of education is basic to face the opportunities and potential problems of multiculturalism. In Spain educational system is decentralized, therefore, the different autonomous regions can establish laws related to education within their territories. The model of multicultural education in Castilla La Mancha is directly related to social cohesion and has a commitment to inclusive education. This implies the transformation of teaching practices, as well as changes in the schools’ culture and organization. Intercultural education pursues equity, intercultural competence, social transformation and the fight against discrimination. An inclusive school is characterized by a high commitment of teachers and a positive attitude towards heterogeneous groups, because they are the reflection of our society. This will result into an effort to offer human, material or technical, support in the ordinary classroom.